The Value of Plutonium - Cement Fallout for Health Protection in A Dense Oncological Landscape - Elements for Systematization - Pirot, Florent (European Journal of Applied Sciences, 2023)
This article proposes paths for further medical treatment with nuclear means, developing on results achieved in a varsity of fields, resulting not only on personal observations from the author but also on large scale epidemiological data spilling from Google enquiries. Various cancers, especially in the bottom half of the body, are shown to be healed through that peculiar way, with some results inviting for the top half, for cardiovascular health, and for cecity altogether.